Rejim anti-money laundering di Indonesia - Nasution, Bismar, 1957-; Indonesia; Indonesia (Bandung : BooksTerrace & Library, 2005)
Legal instruments for combating money laundering and their implementation in Indonesia.
Includes the text of: Undang-Undang Tentang Tindak Pidana Pencucian Uang and Undang-Undang Tentang Perubahan atas Undang-Undang nomor 15 tahun 2002 Tentang Tindak Pidana Pencucian Uang.
Includes bibliographical references (p. 143-144) and index.
Keywords: Money laundering -- Indonesia